Development of speed trap programming model using microcontroller - Abd Rahman, Zulkifli; Wan Hasan, Wan Zuha; Hasan, Mohd Khair (Universiti Putra Malaysia Press, 2002)
In this modern day, many speed traps have been developed to detect speed of passing vehicles. Various speed traps including laser and radar gun technology, often being used nowadays. This technology, for example laser speed gun emits a very narrow, intense beam of "invisible' light. The speed of light is a known constant (approximately 300 OOO-km persecond). Therefore, the laser speed gun calculates distance by measuring the length of time it takes for the beam to travel to a target and back to the gun. Other types include hand held radar, movable and fixed speed cameras.